Experimental and Numerical Study of At-Rest Lateral Earth Pressure of Overconsolidated Sand - Magdi El-Emam (Advances in Civil Engineering)
The paper presents a one-meter-height rigid facing panel, supported rigidly at the top and bottom to simulate nonyielding retaining wall system. A set of load cells is used to measure the horizontal force at the top and bottom of the facing panel, which is converted to equivalent horizontal earth pressure acting at the back of the wall. Another set of load cells is used to measure the vertical load at the bottom of the wall facing, both at the toe and the heel. Uniformly graded sand was used as backfill soil. The measured wall responses were used to calibrate a numerical model that used to predict additional wall parameters. Results indicated that the measured horizontal earth force is about three times the value calculated by classical at-rest earth pressure theory. In addition, the location of the resultant earth force is located closer to 0.4 H, which is higher compared to the theoretical value of H/3. The numerical model developed was able to predict the earth pressure distribution over the wall height. Test set up, instrumentation, soil properties, different measured responses, and numerical model procedures and results are presented together with the implication of the current results to the practical work.